On the anticancer clinical activity of perillyl alcohol and limonene: A critical assessment of the outcomes - Paula G Santos; Francisco JR Paumgartten; Antonio C Siani (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2022)
Monoterpenes with p-menthane structure (perillyl series) can inhibit Ras-proteins prenylation involved in carcinogenesis processes. To evaluate the safety and efficacy of perillyl alcohol (POH) and limonene to treat any type of human cancer, we conducted a systematic review of clinical studies found in seven biomedical bibliographic databases and four clinical trial registries. After screening titles, abstracts, and full texts for inclusion/exclusion criteria, one study on limonene (oral) and 19 on POH administered by oral (13), dermal (2), or intranasal-instillation routes (4), comprising phase I or I/II trials, were included in the review. The quality of included studies was assessed as well. No randomized and controlled phase-III trial was performed or is in progress. A critical appraisal of study results suggested that both compounds are safe after oral ingestion, dermal application, or nasal instillation. Overall, phase II studies showed no evidence of anticancer activity. Nasal instillation of POH, however, apparently prolonged the overall survival of patients with glioblastoma. Randomized and controlled (phase III) clinical studies are necessary to confirm these findings.